Race and identity of Brazilians in South Africa: an ethnographic study on racialization, habitus, and intersectionality - Campos, Anita (Social Anthropology, 2019)
Despite recurrent academic interest in the study of race in both South Africa and in Brazil, little work has been done in Anthropology about the two countries of the Global South in relation to each other. This thesis is situated in that gap and presents an ethnographic study about the racialised experiences of Brazilian migrants in South Africa, in order to explore the different processes of racialization that occur in South Africa and Brazil. The first part of the investigation focuses on the conflictual encounter between informants’ internalized racial habitus as learned in Brazil with the one they encounter in South Africa. The second part examines the impact that such racialization has on the racial identity of Brazilian individuals. Informants found themselves in situations of racial ambiguity in which they did not fit perfectly in any of the local racial categories, and were classified by South Africans in different (and sometimes multiple) racial categories from their previous one in Brazil. I use the theoretical lens of intersectionality to explore informants’ reflections on 'what they are’ as they socially adapted to South African racial categorisations and habitus.